Slope Stability in Gombel Lama: A Comparative Analysis of Peak, Fully Softened, and Residual Conditions - Andriansyah, Arief; Mulyono, Muhammad Nafi’; Aulia, M. Rafi (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2025)
Landslide could be incident that bring a lot of loss, as an example was fatalities and public activity would be disturb. It makes engineers to can identify a slope condition and evaluated what is most effective soil reinforcement necessary. Semarang has several of topography, one of them is Gombel Lama. Gombel Lama was formed ramp which has precipitous slope. The research aim of identificate slope soil parameter in several conditions, as peak, fully softened, and residual. To determine slope safety factor of Gombel lama, researchers does two types of soil investigastion. There are field investigation, they were Standart Penetration Test and Inclinometer and laboratory investigation , that was Direct Shear Test. From field investigation data, it done soil stratification. Furthermore, it combined with Direct Shear Test’s result, researchers use Plaxis LE to make slope stabilities simulation so that assign safety factor of slope is 2.39 (peak), 1.21 (fully softened), 0.53 (residual), and 0.87(average between fully softened and residual). The research result assign that safety factor of slope was decreased while fully softened and residual conditions. Therefore, it is determination of soil reinforcement design not only use peak soil parameter, but also have to heed soil parameters of fully softened and residual conditions.